Pendampingan Pembuatan Video Promosi Wisata Alam Curug Terambon Kepahiang Provinsi Bengkulu Berbasis Digital - Octaviani, Vethy; Yanto, Yanto (Jurnal Dehasen Untuk Negeri, 2025)
Kepahiang Regency, Bengkulu Province has many beautiful and easily accessible tourist destinations, one of which is in Pagar Gunung Village, Kepahiang District. This village has a stunning natural tourist attraction, namely Curug Terambon with the charm of a waterfall that flows freely between piles of beautiful rocks. Developing tourism potential and increasing tourism promotion is an important priority program to be carried out in order to improve the economy of village communities. And to make all this happen, it is necessary to get support from all village communities, especially youth, by utilizing various digital platforms, namely increasing tourism promotion on social media. Therefore, Lecturers and Students of the Communication Science Study Program, Faculty of Social Sciences, Dehasen Bengkulu University carried out community service activities to help the youth of Pagar Gunung Village in their efforts to introduce the village's potential to the wider community through assistance in making digital-based tourism promotional videos. Through making this video, the charm of Curug Tarambon as a potential tourist attraction for Pagar Gunung Village can be explored. This activity went well and is expected to provide benefits, namely increasing the capacity of the youth of Pagar Gunung Village, especially the skills of making videos by utilizing the cellphone media they have, where the results of video production can be used as promotional media so that they can help introduce the village's potential to the wider community.